Influence mechanism of pore environment characteristics on ultrasonic wave velocity of kaolin - Lihaolin JIN; Min ZHANG; Chengwang YUAN; Zhan WANG (Shuiwen dizhi gongcheng dizhi, 2023)
Kaolin is a common clay in engineering. The microstructure of kaolin is very sensitive to the change of pore environment. At present, the research on the relationship between pore environment characteristics and acoustic wave velocity of kaolin remains to be further studied. In this paper, based on the ultrasonic test theory, RSM-SY6 ultrasonic detector is used to study the change rule of ultrasonic wave velocity of kaolin under different pore environment conditions. In addition, the influence mechanism of pore environment characteristics on ultrasonic wave velocity of kaolin is analyzed from the microscopic perspective of the arrangement mode of clay particles and the interaction between clay particles and pore solution. The results show that (1) the ultrasonic wave velocity of kaolin decreases with the increasing void ratio. (2) With the increasing water content, the ultrasonic wave velocity of kaolin decreases slightly at first and then increases greatly. (3) The effect of pore solution pH value on ultrasonic wave velocity of kaolin is related to the edge isoelectric pH value. When the pore solution pH value is equal to the edge isoelectric pH value, the ultrasonic wave velocity is the maximum. (4) The addition of salt reduces the ultrasonic wave velocity of kaolin. When the concentration of saline solution ranges from 0 to 0.5 mol/L, the wave velocity decreases rapidly. Under the same anion condition, the high valence cation has a more obvious effect on the reduction of ultrasonic wave velocity. This paper provides a reference for the study of the acoustic characteristics of viscous soil, and also provides a theoretical basis for the application of ultrasonic detection technology in soil.